Feldenkrais method on neck and low back pain to the type of exercises and outcome measurement tools: A systematic review - Vikram Mohan (2018)
© 2016 Warmińsko-Mazurska Izba Lekarska w Olsztynie Introduction Feldenkrais method (FM) has been applied on a large number of people as an educational method to create awareness of themselves and of their own body postures. Despite several existing FM studies, there has not yet been a review of FM in the context of musculoskeletal disorders. Aim This review aimed at determining the effect, type of exercises, duration and the outcome measure utilized in assessing the FM among individuals with neck and low back pain (LBP). Material and methods Four databases were searched for eligible studies, which were published in the years 1999–2015. Two authors individually assessed selected studies. From a total of 165 articles, 3 articles were selected and another 1 article from other resources with a total of 4 articles. Results and discussion The number of participants in all of the four included studies were 65.5 ± 30.1 (mean ± SD). The quality of the studies that was assessed using Physiotherapy Evidence Databases (PEDro) scale revealed the score of at least 5/10. Evidence exists that FM may be used for treating musculoskeletal disorders. However, the studies were not enough to make a decision because of different selections of FM lessons, duration and outcome measures. The review also determined type of exercises and outcome utilized in assessing the benefit of FM. Conclusions Overall, judging from the increasing number of articles in recent years related to FM, this review reports sufficient evidence that FM is increasingly being used in the management of neck pain and LBP.